Unusual Presentation of Hepatocellular Carcinoma into Right iliac fossa: A Rare Entity - Murali Uthamalingam; Karthikumaran Periyasamy (Journal of Clinical and Diagnostic Research, 2015)
Hepatocellular carcinoma (HCC) is the most common primary malignant hepatic tumour. Hepatocellular carcinoma presenting itself or extending into the right iliac fossa (RIF) is a very rare entity. We report on a rare case of hepatocellular carcinoma in a 60-year-old lady, presented with a mobile mass in the lower abdomen without cirrhosis, with normal α-feto protein levels (AFP) or any known risk factors for liver disease. HCC in this case was unusual in its presentation both in the patient as well as a disease.